Influence of Electrode Surface Area and Processing Time on Chemical Oxygen Demand (COD) and Total Suspended Solid (TSS) Reduction in Tofu Wastewater Using Electrocoagulation - Dani Faizal; Anila Wirantika; Neni Damajanti (Research in Chemical Engineering, 2024)
Electrocoagulation is a wastewater treatment process that uses electrochemical working principles to remove contaminants in solutions or wastewater. Where at the anode (negative current) metal ions are released into solution, while at the cathode (positive current) an electrochemical reaction occurs, namely the release of H2 (hydrogen) gas. Factors that influence the electrocoagulation process include electrode type, current strength, electrode cross-sectional area, process time, voltage, stirring, distance between electrodes, and acidity level (pH). The objective of this research is to investigate the effect of the surface area of the electrode and processing time on the COD and TSS of tofu wastewater.  In this research, tofu industry liquid waste was processed using the electrocoagulation method using fixed variables including, Fe-Fe type electrodes, 4 electrodes, acidity level at 4, tofu liquid waste temperature at 25 ̊ C, distance between electrodes 2 cm, electrode thickness 2 mm, test sample of 4 liters and current strength of 13 V. The changing variables used are electrode cross-sectional area (70 cm² and 60 cm²) and processing time (30, 45, 60, 75, 90 minutes).  In this study, the best conditions for reducing COD and TSS levels were obtained with a cross-sectional area of ​​70 cm² and a process time of 60 minutes for reducing COD levels and 30 minutes for reducing TSS levels. With a reduction in COD levels of 690.66 mg/L and a reduction in TSS levels of 181.25 mg/L. The results of reducing COD levels do not meet the tofu industry wastewater quality standard of 300 mg/L, and the results of reducing TSS levels meet the tofu industry wastewater quality standard of 200 mg/L.